Identification and characterization of a Golgi retention signal in feline coronavirus accessory protein 7b - Florek, Dominik (J Gen Virol, 2017)
Feline coronaviruses encode five accessory proteins with largely elusive functions. Here, one of these proteins, called 7b (206 residues), was investigated using a reverse genetic approach established for feline infectious peritonitis virus (FIPV) strain 79–1146. Recombinant FIPVs (rFPIVs) expressing mutant and/or FLAG-tagged forms of 7b were generated and used to investigate the expression, processing, glycosylation, localization and trafficking of the 7b protein in rFIPV-infected cells, focusing on a previously predicted ER retention signal, KTEL, at the C-terminus of 7b. The study revealed that 7b is N-terminally processed by a cellular signalase. The cleavage site, 17-Ala|Thr-18, was unambiguously identified by N-terminal sequence analysis of a 7b processing product purified from rFIPV-infected cells. Based on this information, rFIPVs expressing FLAG-tagged 7b proteins were generated and the effects of substitutions in the C-terminal (202)KTEL(206) sequence were investigated. The data show that (i) 7b localizes to and is retained in the medial- and/or trans-Golgi compartment, (ii) the C-terminal KTEL sequence acts as a Golgi [rather than an endoplasmic reticulum (ER)] retention signal, (iii) minor changes in the KTEL motif (such as KTE, KTEV, or the addition of a C-terminal tag) abolish Golgi retention, resulting in relocalization and secretion of 7b, and (iv) a KTEL-to-KDEL replacement causes retention of 7b in the ER of rFIPV-infected feline cells. Taken together, this study provides interesting new insights into an efficient Golgi retention signal that controls the cellular localization and trafficking of the FIPV 7b protein in virus-infected feline cells.